Corporate Governance and Environmental & Social Governance Practices: An Empirical Analysis of Companies Listed on the Pakistan Stock Exchange - Dr Abdul Rehman ,; Syed Muhammad Adnan,; Rizwan Ali, (Dialogue Social Science Review (DSSR), 2025)
This study examines the influence of the Chief Executive Officer's personal and professional characteristics on research and development spending and corporate environmental and social governance practices in Pakistan. The study investigates 150 listed firms in the Pakistan Stock Exchange from 2015 to 2022. The study employed regression analysis OLS, fixed effects, and random effects to comprehensively investigate the nexus between CEO characteristics, research and development spending, and firm ESG commitments. The empirical estimations denoted that CEO tenure and duality negatively affect the firm R&D spending and ESG practices. While CEO education and experience support the firm R&D spending significantly contributed towards the corporate ESG commitments. Moreover, the aged CEOs also found hesitant to follow and invest in the technological trends and ESG activities. The study also finds that firm size positively affects firm spending on R&D along with corporate ESG practices, while firm leverage has a negative impact on R&D spending and ESG activities. The findings of this study provide valuable insights for scholars, business owners, investors, business elites, and policymakers in Pakistan and other developing economies with similar corporate governance mechanisms